MRI findings in cranial eumycetoma - Ahmed, Munawwar; Sureka, Jyoti; Chacko, Geeta; Eapen, Anu (Indian Journal of Radiology and Imaging, 2011)
Cranial eumycetoma (CE) due to direct inoculation of Madurella grisea into the scalp is extremely rare. We describe a case of CE caused by direct inoculation of M. grisea with the characteristic MRI findings of the "dot-in-circle" sign and a conglomeration of multiple, extremely hypointense "dots."
Keywords: “Dot-in-circle” sign; eumycetoma; Madurella grisea; magnetic resonance imaging